Thermal adaptation of photosynthetic physiology of the invasive vine Ipomoea cairica (L.) enhances its advantage over native Paederia scandens (Lour.) Merr. in South China. (20th December 2022) - Chen, Minghao; Cai, Mingling; Xiang, Ping; Qin, Zhangfen; Peng, Changlian; Li, Shaoshan
Abstract:  : Ipomoea cairica (L.) Sweet is an invasive vine in South China with strong ecological adaptability in tropical and subtropical ecosystems. However, its invasion mechanism under global warming still remains unknown. In the present study, the thermal adaptability of I. cairica was investigated from the perspective of photosynthetic physiology to explain its successful invasiveness in South China, compared to a niche-overlapping native vine Paederia scandens (Lour.) Merr. Results of field photosynthesis measurements indicated a higher photosynthesis of I. cairica than P. scandens, which was also more temperature-sensitive. Under heat treatment (40 °C), the thermal-avoidance strategy of P. scandens and the thermal-adaptation strategy of the I. cairica enhanced the photosynthetic growth advantage of I. cairica over P. scandens . In I. cairica, the increase of soluble sugar and antioxidant enzyme activity along with the decrease of Malondialdehyde and oxide accumulation demonstrated that I. cairica has superior thermal-adaptation, contrary to P. scandens . Expression of IcOr and IcSRO1 in I. cairica was induced at 40 °C, maintaining the stability of photosynthetic system II and enhancing antioxidant ability. Out study suggested that a higher frequency of heat disturbance under global warming will enhance the invasion capability I. cairica but inhibit the native vine P. scandens . Highlight: This paper reveals that contrary thermal-adaptation strategies expanded the photosynthetic, growing, and physiological advantages of invasive I. cairica over native P. scandens under high temperature.